2015
DOI: 10.3892/mmr.2015.3557
|View full text |Cite
|
Sign up to set email alerts
|

An integrated analysis of the effects of microRNA and mRNA on esophageal squamous cell carcinoma

Abstract: Esophageal squamous cell cancer (ESCC) is an aggressive type of cancer with poor prognosis and leading to decreased quality of life. The identification of patients at increased risk of esophageal squamous cell cancer may improve current understanding of the role of micro (mi)RNA in tumorigenesis, since the miRNA pattern of these patients may be associated with tumorigenesis. In the present study, the miRNA and mRNA expression profiles of ESCC tissue samples and adjacent normal control tissue samples were obtai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 44 publications
3
13
0
Order By: Relevance
“…However, other evidence highlights FNDC3B as oncogene. First, FNDC3B is usually amplified [7, 33] and highly expressed in HCC and other cancers [7, 31, 3436]. Cai et al .…”
Section: Discussionmentioning
confidence: 99%
“…However, other evidence highlights FNDC3B as oncogene. First, FNDC3B is usually amplified [7, 33] and highly expressed in HCC and other cancers [7, 31, 3436]. Cai et al .…”
Section: Discussionmentioning
confidence: 99%
“…Effects of NS5ABP37 on cell proliferation, apoptosis , and cycle distribution . Previous studies reported that NS5ABP37 is associated with human cancers such as HCC, esophageal squamous cell cancer, glioblastoma, primary urethral clear‐cell adenocarcinoma, chronic lymphocytic leukemia, and prostate cancer . Therefore, we attempted to further study the effect of NS5ABP37 on the growth of cancer cells as well as normal hepatocytes.…”
Section: Resultsmentioning
confidence: 99%
“…FNDC3B is one of the most common genes up-regulated in cancer tissues, regardless of the cancer type and tumor origin [18]. Recent studies have found that FNDC3B is highly expressed in breast cancer, esophageal cancer, glioblastoma, and hepatocellular carcinoma, and is associated with cancer cell proliferation, invasion and metastasis [19][20][21][22][23]. Therefore, we hypothesized that FNDC3B promotes cell migration and tumorigenesis in PC.…”
Section: Introductionmentioning
confidence: 98%